Ethnopharmacological basis for antispasmodic, antidiarrheal and antiemetic activities of Ceratonia siliqua pods (Bangladesh Journal of Pharmacology, 2017)
The study was conducted to provide the ethnopharmacological bases of the crude extract of seed pods of Ceratonia siliqua in the gastrointestinal spasm, diarrhea and emesis. In segregated rabbit jejunum, it showed dose-dependent (0.01-10 mg/mL) relaxation of spontaneous as well as carbachol (1 µM)-induced contraction. Pre-treatment of segregated rat ileum with C. siliqua, significantly (p